Improvements to the quality of underground water by introducing carbon dioxide - Poberžnik, Mojca (Acta geotechnica Slovenica, 2008)
The presented research work is focused on the development of an innovative way of economically improving the quality of underground water by the application of carbon dioxide. The basic pilot plant was developed with the idea of applying carbon dioxide in order to maintain the carbonate equilibria in water, pumped from under the ground. The optimal content of this natural component in underground water, used in urban areas for different purposes (e.g. drinking water, heating systems etc), simultaneously prevents corrosion and precipitated mineral deposits. The adaptation of an existing pilot plant started with operational testing and preliminary measurements. An appropriate sensor system for the online monitoring of the tap waterćs heating process measuring parameters such as the temperature, the concentration of dissolved carbon dioxide, the conductivity and the pH value was built in. Different amounts of carbon dioxide were applied during the two experimental stages. The composition of the water was regularly analysed using automatic titration and ionic chromatography. The gas-dosing control in the first phase was volumetric. Due to an observed inaccuracy in the gasdosing system, the volumetric dosing control was replaced with a system for the mass control of the introduced gas. Closing the system was considered to be suitable, as the water composition remained almost constant during the entire experiment. Improvements to the gas-dosing control and the closing of the system were carried out in the final phase of the pilot plantćs adaptation. Further measurements were made in different seasons to test the seasonal influences onunderground water's composition and the efficiency of the carbon dioxide supply.
Keywords: karbonati; kemijska analiza; kvaliteta vode; ogljikov dioksid; pitna voda; podzemna voda